Vattimo’s Renunciation of Violence - Lindsey, Jason Royce (Ethical theory and moral practice, 2013)
For Gianni Vattimo, the renunciation of violence is the starting point for constructing a post foundational politics. So far, criticism of Vattimo’s argument has focused on his larger commitment to metaphysical nihilism and whether the renunciation of violence is a thicker principle than his post foundational philosophy can support. I argue that Vattimo’s renunciation of violence can also be criticized for two other reasons. First, Vattimo attempts to distinguish between acceptable and unacceptable uses of violence through an under developed idea of self-defense. Second, despite his attention to the political and philosophical impact of mass communications technology, Vattimo ignores emerging technological challenges to our understanding of violence. Nonetheless, I argue that Vattimo’s renunciation can still serve as a useful starting point for contemporary political thinking. What Vattimo’s logic shows is that we can enhance the moral standing of democracy by decisively detaching its practices and institutions from historical artifacts of political violence.